Pd Uptake and H2S Sensing by an Amphoteric Metal–Organic Framework with a Soft Core and Rigid Side Arms1. Issue 52 (3rd November 2014) - Cui, Jieshun; Wong, Yan‐Lung; Zeller, Matthias; Hunter, Allen D.; Xu, Zhengtao
Abstract Molecular components of opposite character are often incorporated within a single system, with a rigid core and flexible side arms being a common design choice. Herein, molecule L has been designed and prepared featuring the reverse design, with rigid side arms (arylalkynyl) serving to calibrate the mobility of the flexible polyether links in the core. Crystallization of this molecule with PbII ions led to a dynamic metal–organic framework (MOF) system that not only exhibits dramatic, reversible single‐crystal‐to‐single‐crystal transformations, but combines distinct donor and acceptor characteristics, allowing for substantial uptake of PdCl2 and colorimetric sensing of H2S in water.